Development of the self-regulation assessment and content validation using cognitive interviews in a multicultural post-rehabilitation population - Tanja Mol; Tanja Mol; Eline Scholten; Coen van Bennekom; Coen van Bennekom; Marcel Post; Marcel Post (Frontiers Media S.A., 2023)
AimSelf-regulation is one of the main goals of medical rehabilitation. Four themes of self-regulation were identified by former patients and rehabilitation physicians in a previous study. Based on these themes, a measure for self-regulation, the self-regulation assessment (SeRA), was developed. This study aimed to establish the content validity of the SeRA in a multicultural and multi-diagnostic post-rehabilitation population.MethodsThe Consensus-based Standards for the selection of health Measurement Instruments (COSMIN) methodology was applied. First, cognitive interviews were held with eight former rehabilitation patients. Feedback was obtained on relevance, comprehensibility, and comprehensiveness of the items. Items with problems were revised. Then, a second series of cognitive interviews was held with 16 former rehabilitation patients with non-Western migration backgrounds. Again, feedback was obtained on relevance, comprehensibility, and comprehensiveness of the items.ResultsThe first series of cognitive interviews revealed good comprehensiveness, and also comprehensibility or relevance problems with 12 of the 25 items. These items were revised or deleted. Two missing concepts were identified and these were added. There was no need to revise the items based on the results of the second series of cognitive interviews.ConclusionThe final version of the SeRA demonstrated content validity for the studied population. The measure is ready for psychometric analyses in subsequent validation studies.